Pentagon history purge highlights which stories are told and why others are ignored - Geoff Bennett (2025)
The Trump administration’s efforts to strip diversity, equity and inclusion prompted the Defense Department to remove thousands of pages and images honoring the contributions of women and people of color. The Pentagon is restoring some of those web pages, saying the removal was a mistake.
United States of America